Jatropha curcas latex inhibits the release of collagenase by gingival fibroblast (Medical Journal of Indonesia, 2007)
Folkloric use of J. curcas latex among others are to cure tooth pain, bleeding gum and as anti-inflammatory drug. Collagenase is a neutral protease released by activated macrophage and also by fibroblasts in small amounts. The aim of this study was to evaluate the effect of J. curcas latex on collagenase released by fibroblasts. Four doses of J. curcas latex from 37.5-300 g/ml were added to 3 human gingival primary fibroblast cell culture. After 1 to 4 days of incubation, collagenase in the supernatant was assayed with collagen. The degradation products were then separated by SDS-PAGE and the density of ¾ αA bands were measured semi quantitatively by Adobe Photo computer program. Result showed that J. curcas latex decreased collagenase released by human gingival fibroblast, and increasing dose inhibits more. It may be concluded that the latex of J. curcas inhibits the release of collagenase by human gingival fibroblast. (Med J Indones 2007; 16:219-23)